2022
DOI: 10.2147/ndt.s358851
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Low-Dose Rituximab in Anti-MuSK Myasthenia Gravis Patients: A Retrospective Study

Abstract: Purpose To evaluate the efficacy and safety of low dosages of rituximab (RTX) in the treatment of MuSK-antibody-positive MG patients. Patients and Methods We retrospectively analyzed the data of MuSK-antibody-positive MG patients who were treated with low dosages of RTX from January 2018 to October 2021. The long-term treatment response to RTX was assessed by Myasthenia Gravis Foundation of America (MGFA) post-interventional status (PIS), Myasthenia Gravis Status and Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Evidence supports the use of monoclonal antibody therapy such as rituximab as an early therapeutic option in MuSK-MG patients with poor responses to steroids [ 1 , 7 , 8 ]. Patients with MuSK-MG receiving rituximab show sustained clinical improvement, as in our case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence supports the use of monoclonal antibody therapy such as rituximab as an early therapeutic option in MuSK-MG patients with poor responses to steroids [ 1 , 7 , 8 ]. Patients with MuSK-MG receiving rituximab show sustained clinical improvement, as in our case.…”
Section: Discussionmentioning
confidence: 99%
“…The use of acetylcholinesterase inhibitors for symptomatic treatment is generally unsatisfactory in MuSK-MG patients. Steroids and immunosuppression therapy have a better response, and monoclonal antibodies such as rituximab therapy showed greater and sustained outcomes in MuSK-MG patients [ 1 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…One patient relapsed among three patients whose CD27+ B-cell counts were >0.05% at 6 months. On the other hand, clinical relapses occurred even though B cells were depleted ( 172 ). Collectively, we could not reach a definite conclusion regarding the B lymphocytes number in patients and the recurrence of clinical symptoms.…”
Section: Therapeutic Options In Musk Myasthenia Gravismentioning
confidence: 99%
“…The patient was diagnosed with Morvan’s syndrome and treated with IVIG at a dose of 0.4 g/kg/day for 5 days and oral steroids; however, his symptoms of myokymia and insomnia did not improve 1 month later. Considering that the patient’s immune test indicated that he was in an immunosuppressive state at the time, he was treated with low-dose rituximab ( 7 , 8 ) at a dose of 100 mg/week for 4 weeks. During the follow-up 1 month later, the muscle twitching, limb pain, and insomnia symptoms were significantly improved.…”
Section: Case Presentationmentioning
confidence: 99%